Hacktech COVID-19: Case study of a virtual hackathon in Latin America - Cabrera, Ronny; Calderón, Carlos; Carrión, Andrea (ACI Avances en Ciencias e Ingenierías, 2021)
This case study presents the Hacktech COVID-19 initiative, a project that aimed to develop an online hackathon that allows generating technology-based solutions that contribute to solving the health, social and economic crisis caused by COVID-19. For the event, a call was made to entrepreneurs and innovators from Latin America and the world to present solutions on the issues raised. Through the assignment of mentors, advice was provided for each team to improve their proposals. The authors used the Health Hackathon Handbook as a model to organize the event, and adapted it to generate a completely virtual methodology. Among the most important results of this initiative, the participation of 1,021 people from 25 countries was achieved, the event had the participation of 239 mentors from 23 countries. At the end of the hackathon, 156 projects were presented, of which 78% addressed solutions for health, 9% solutions to protect the community and 13% solutions to protect employment. A jury selected 3 winning projects who received a financial grant for the development of the prototype of their business idea, in addition 15 projects were selected to receive advice on obtaining funds from different sources of financing.
Keywords: hackathon; COVID-19; innovation; hackathon online